Physics and technology of heterojunction devices - Morgan, D. V.; Williams, Robin H. (London, United Kingdom Institution of Engineering and Technology, 1991)
The book draws on the knowledge of various experienced academics, and covers aspects of the physics of heterojunctions, resonant tunnelling effects in semiconductor heterojunction devices, characterisation of heterojunctions, high electron mobility transistors, heterojunction bipolar transistors, and heterostructures in semiconductor lasers.
Electronic reproduction.
Keywords: Semiconductors -- Junctions; Electronic books